2017
DOI: 10.1177/1066896917709350
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Secretory Carcinoma With High-Grade Transformation, CDKN2A/B Loss, Distant Metastasis, and Lack of Sustained Response to Crizotinib

Abstract: High-grade salivary gland secretory carcinoma can have a biphasic appearance on MRI. Diagnosis is confirmed by the histologic appearance and associated ETV6-NTRK3 fusion. Additional molecular genetic events leading to transformation are unknown; however, loss of CDKN2A/B may have contributed. Treatment with multimodal chemotherapy was of limited benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 23 publications
3
32
0
1
Order By: Relevance
“…Cipriani et al . recently published on CDKN2A/B loss in a case of salivary gland mammary secretory analogue carcinoma . Therein, the investigators demonstrated the loss of the tumour suppressor genes in a tumour with high‐grade transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cipriani et al . recently published on CDKN2A/B loss in a case of salivary gland mammary secretory analogue carcinoma . Therein, the investigators demonstrated the loss of the tumour suppressor genes in a tumour with high‐grade transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Cipriani et al recently published on CDKN2A/B loss in a case of salivary gland mammary secretory analogue carcinoma. 57 Therein, the investigators demonstrated the loss of the tumour suppressor genes in a tumour with high-grade transformation. In both cases, loss of these genes led to the dysregulation of the cell cycle and aggressive nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…High grade transformation is a rare phenomenon that has been described in an expanding list of salivary gland carcinomas [26], including SCs. To date (including the current case), HGT has been reported in seven patients of SCs [10,20,[27][28][29]. The sites of origin of these cases were parotid gland (n = 3), palate (n = 1), buccal space (n = 1), sinonasal tract (n = 1, the current case), and unspecified (n = 1).…”
Section: Discussionmentioning
confidence: 78%
“…In SC, the first case of HGT was reported by Jung et al, the authors noted the histological feature resemble to high-grade differentiated acinic carcinoma [17]. As far as I searched, only 16 cases HGT SC has been reported [7,8,11,[17][18][19][20][21]. Histologically, the high-grade transformation area is characterized by solid growth with atypical tumor cells and the high-grade transformation area with comedo necrosis adjacent to follicular structure site tend to demonstrate a more aggressive nature and ultimately a poor prognosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…The high-grade transformation behaves more aggressively and is more associated with a poor prognosis than a low-grade tumor. SC with high-grade histology is rare and only 16 cases have been reported to this date [7,8,11,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%